Analisis Kemampuan Awal Literasi Lingkungan Mahasiswa dalam Pembelajaran Kimia Lingkungan - Al Idrus, Syarifa Wahidah; Rahmawati, Rahmawati (ANWARUL, 2021)
This study aims to determine the initial environmental literacy ability of prospective chemistry teacher students in environmental chemistry courses. This research is a descriptive research with a quantitative approach. The research population is 90 students who take environmental chemistry MK. The sample is a saturated sample, so all the population is used as the research sample. The results showed that the initial ability of prospective chemistry teacher students from the three indicators observed was Concern for the environment with an average score of (3.10) categorized as moderate. Knowledge of the environment with an average score of (3.35) is categorized as moderate. The application of environmental knowledge with an average score of (3.8) is categorized as good.